Cryptotanshinone attenuates LPS-induced acute lung injury by regulating metabolic reprogramming of macrophage - Ye, Zesen; Wang, Panxia; Feng, Guodong; Wang, Quan; Liu, Cui; Lu, Jing; Chen, Jianwen; Liu, Peiqing (Frontiers in Medicine, 2023)
Background Acute lung injury (ALI) is a life-threatening inflammatory disease without effective therapeutic regimen. Macrophage polarization plays a key role in the initiation and resolution of pulmonary inflammation. Therefore, modulating macrophage phenotype is a potentially effective way for acute lung injury. Cryptotanshinone (CTS) is a lipophilic bioactive compound extracted from the root of Salvia miltiorrhiza with a variety of pharmacological effects, especially the anti-inflammatory role. In this study, we investigated the therapeutic and immunomodulatory effects of CTS on ALI. Materials and methods The rat model of ALI was established by intratracheal instillation of LPS (5 mg/kg) to evaluate the lung protective effect of CTS in vivo and to explore the regulation of CTS on the phenotype of lung macrophage polarization. LPS (1 μg/mL) was used to stimulate RAW264.7 macrophages in vitro to further explore the effect of CTS on the polarization and metabolic reprogramming of RAW264.7 macrophages and to clarify the potential mechanism of CTS anti-ALI. Results CTS significantly improved lung function, reduced pulmonary edema, effectively inhibited pulmonary inflammatory infiltration, and alleviated ALI. Both in vivo and in vitro results revealed that CTS inhibited the differentiation of macrophage into the M1 phenotype and promoted polarization into M2 phenotype during ALI. Further in vitro studies indicated that CTS significantly suppressed LPS-induced metabolic transition from aerobic oxidation to glycolysis in macrophages. Mechanistically, CTS blocked LPS-induced metabolic transformation of macrophages by activating AMPK. Conclusion These findings demonstrated that CTS regulates macrophage metabolism by activating AMPK, and then induced M1-type macrophages to transform into M2-type macrophages, thereby alleviating the inflammatory response of ALI, suggesting that CTS might be a potential anti-ALI agent.